Creep in Oedometer for Marine Clay Soil - Hashim, Muhammad Adib (Universiti Teknologi PETRONAS, 2018)
A series of soil investigation including laboratory and in-situ tests has been carefully done to expand the understanding of marine clay behavior around the coastal region of Malaysia. Around this country coastal region, several researches had been conducted to investigate the soil properties of marine clay soil. Due to rapid development in this developing country, there are a great number of construction involving marine clay soil at the coastal region. Deformation of marine clay soil is one of the important factors that engineers need to predict before the construction began and a lot of studies on clay deformation had been conducted. However, the studies of long term deformation of soil or creep is certainly been neglected. The deformation of soil due to creep condition over the constant load is a major challenge for soil engineering. In geotechnical engineering studies, soil will deform over time when it is subjected to certain loading. Thus, the author highlight the interest to study the geotechnical properties of marine clay at Sarawak Field and creep behavior of this marine clay sample under various constant loading where oedometer tests were conducted to determine the creep pattern in marine clay sample.